2021
DOI: 10.1002/hep.32037
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Splenic Artery Embolization to Treat Refractory Ascites in a Patient With Cirrhosis

Abstract: ince the early 1970s several studies have reported distal splenic artery embolization, better known as partial spleen embolization (PSE), as an efficacious treatment of portal hypertensive variceal bleeding and hypersplenism in cirrhosis. (1,2) However, the effect of PSE on portal pressure is secondary to the induction of splenic infarction. Depending on both the infarct volume and possible infection, PSE can induce serious complications including death. (2,3) On the other hand, proximal splenic artery emboliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Our study also demonstrates that SAE can decrease RIs. This data is in line with other studies that have revealed similar findings in improved RIs and hepatic arterial blood flow [ 7 - 10 ]. As mentioned, RIs frequently increase following an OLT, notably in the setting of portal hypertension [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study also demonstrates that SAE can decrease RIs. This data is in line with other studies that have revealed similar findings in improved RIs and hepatic arterial blood flow [ 7 - 10 ]. As mentioned, RIs frequently increase following an OLT, notably in the setting of portal hypertension [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…Partial splenic embolization (PSE) in cirrhosis is mostly used for the treatment of complications of portal hypertension in patients without alternative options and in those with left-sided portal hypertension. [143,144] PSE may also be used to treat hypersplenism in the very rare (< 1%) patients with cirrhosis and large splenomegaly, severe thrombocytopenia, and a history of spontaneous bleeding. [145] Unlike platelet transfusions and TPO-R agonists, the effect of PSE on platelet count appears to be more sustained over time.…”
Section: Radiological Interventions To Treat Hypersplenism In Patient...mentioning
confidence: 99%
“…Unlike platelet transfusions and TPO-R agonists, the effect of PSE on platelet count appears to be more sustained over time 144–146 . PSE consists of placing a catheter in the splenic artery and repeatedly injecting embolization particles until the splenic artery blood flow is reduced by ~50% 143,147 . The increase in platelet count is proportional to the extent of splenic infarction and is likely due to a combination between reduced splenic sequestration and destruction, the resulting longer half-life of circulating platelets, and the increased levels of circulating TPO 148 .…”
Section: Thrombocytopenia In Patients With Cirrhosis: Definition Path...mentioning
confidence: 99%
“…Depending on the size of the spleen and, therefore, the amount of blood entering the splenic vein, this mechanism may further contribute to the return of blood from the splanchnic circulation to the right heart. [34,35] In fact, direct measurements of PV blood flow after opening of TIPS show an immediate increase of 64% with a mean absolute increase from 691 to 1136 ml/ min. [18] On the other hand, increased CO also leads to arterial vasodilation of nonsplanchnic vascular beds.…”
Section: Early Hemodynamic Consequences Following Tips Placementmentioning
confidence: 99%
“…In parallel, the sudden decrease of portal pressure reduces the barrier to splenic vein outflow (i.e., resistance to the blood flow in the splenic vein), which increases PV blood inflow. Depending on the size of the spleen and, therefore, the amount of blood entering the splenic vein, this mechanism may further contribute to the return of blood from the splanchnic circulation to the right heart 34,35…”
Section: Pathophysiological Consequences Of Tips Placement In Patient...mentioning
confidence: 99%